Cognitive techniques for ultrawideband communications - Malik, W; Edwards, D (2006)
Cognitive radio is an emerging wireless technology that allows dynamic system reconfiguration, promising dramatic improvements in spectrum utilisation. Unlicensed spectrum sharing is the theme that binds cognitive radio and ultrawideband technologies. This paper presents an assessment of cognitive techniques for ultrawideband systems, highlighting the characteristics of this highly flexible, spectrum efficient regime. The performance improvements expected from cognitive ultrawideband systems are evaluated and the research challenges posed are discussed. © The Institution of Engineering and Technology.